HUBUNGAN VISI DAN MISI SEKOLAH DENGAN PENINGKATAN MUTU KINERJA SEKOLAH - Sumantri, Agus; Gadriaman, Gadriaman; Jayusman, Iyus; Wibowo, Priyo (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This study was conducted in public junior high schools spread across West Java which are quality schools in the district/city, which amounted to 21 schools In this study the author used "Effective Schools, School-Based Quality Improvement Management," as the grand theory. This study is intended to explain the effectiveness of the relationship between the vision, mission and quality of school performance. This study uses quantitative methods with descriptive statistical research models because the sample used is a saturated sample model because the population is less than 30. Data were obtained by distributing valid and reliable instruments to each school, with 8 (eight) respondents per school consisting of: principals and vice principals, Mathematics, Science and English teachers and school committees.  In this study, the independent variable is the vision and mission of the school while the quality of school performance is the dependent variable. In this study the authors found that:  Correlation of vision, school mission based on the results of the analysis showed a moderate/sufficient relationship to the quality of school performance, but did not affect the quality of school performance, this means that the vision and mission of the school did not make an important contribution to the school in improving the quality of its performance. ABSTRAKPenelitian ini dilakukan di SMP Negeri yang tersebar di wilayah Jawa Barat yang merupakan sekolah bermutu di kabupaten/ kota, yang jumlahnya 21 sekolah  Dalam penelitian ini penulis menggunakan ”Sekolah Efektif, Manajemen Peningkatan Mutu Berbasis Sekolah,” sebagai grand theory. Studi ini dimaksudkan untuk menjelaskan efektifitas hubungan antara  visi, misi sekolah  terhadap mutu kinerja sekolah. Penelitian ini menggunakan metode kuantitatif dengan model penelitian statistik deskriptif  karena sampel yang digunakan adalah model sampel jenuh karena jumlah populasinya kurang dari 30. Data diperoleh dengan cara menyebarkan instrument yang valid dan reliabel kepada tiap sekolah, dengan responden tiap sekolahnya 8 (delapan) orang yang terdiri dari : kepala sekolah dan wakil kepala sekolah, Guru Matematika, IPA dan Guru Bahasa Inggris serta Komite sekolah.  Dalam penelitian ini yang menjadi variabel bebas adalah visi, misi sekolah sedangkan mutu kinerja sekolah sebagai variabel terikat. Dalam penelitian ini penulis menemukan hasil  bahwa:  Korelasi visi, misi sekolah  berdasarkan hasil analisis menunjukkan adanya hubungan sedang/cukup terhadap mutu kinerja sekolah, tetapi tidak mempengeruhi mutu kinerja sekolah, hal ini berarti visi dan misi sekolah sekolah tidak memberikan kontribusi penting kepada sekolah dalam meningkatkan mutu kinerjanya.